2016
DOI: 10.1007/s00784-016-1926-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of otologic signs and symptoms in adult patients with temporomandibular disorders: a systematic review and meta-analysis

Abstract: This study intends to provide understanding over the prevalence of otologic signs and symptoms in TMD cases in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 33 publications
3
38
0
1
Order By: Relevance
“…Unfortunately, although the study notes that all patients underwent impedance audiometry, these results were not reported. Porto De Toledo et al performed a systematic review and meta‐analysis on the prevalence of otologic signs and symptoms in patients with TMJD, and in their review of eight studies found that otologic symptoms were quite common: ear fullness (74.8%), otalgia (55.1%), tinnitus (52.1%), vertigo (40.8%), and hearing loss (38.9%) . However, these studies did not quantify or measure the severity of these otologic complaints using a validated outcomes instrument, hence the need for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, although the study notes that all patients underwent impedance audiometry, these results were not reported. Porto De Toledo et al performed a systematic review and meta‐analysis on the prevalence of otologic signs and symptoms in patients with TMJD, and in their review of eight studies found that otologic symptoms were quite common: ear fullness (74.8%), otalgia (55.1%), tinnitus (52.1%), vertigo (40.8%), and hearing loss (38.9%) . However, these studies did not quantify or measure the severity of these otologic complaints using a validated outcomes instrument, hence the need for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some articles reported a high prevalence of tinnitus in patients with TMD, but they did not compare the results with those of healthy controls to see whether there truly exist any significant relationships. Hence, we have performed a systematic study with the aim of determining if there is a higher prevalence of tinnitus in patients with TMDs than in patients without TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] EF was reported to be manifested in approximately 75% of TMD patients. 11 It has been suggested that EF associated with TMD is the result of stomatognathic dysfunction, which transmits unnecessary charges to the middle ear muscles or bony network between the TMJ and middle ear. 12 In spite of this potential underlying mechanism, TMD tends to be neglected by otolaryngologists when evaluating otologic symptoms in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%